New Cultural Histories of India : materiality and practices - New Cultural Histories of India (Conference) (2010 : Centre for Studies in Social Sciences); Chatterjee, Partha; Guha-Thakurta, Tapati; Kar, Bodhisattva; Centre for Studies in Social Sciences (New Delhi: Oxford University Press, 2014)
Most of the papers presented at the conference on 'New Cultural Histories of India', organized by Centre for Studies in Social Sciences during 5-7 January 2010.
The textual -- The visual -- The aural -- The ritual -- The spatial.
Includes bibliographical references and index.
Keywords: INDIA -- CIVILIZATION -- CONGRESSES; INDIA -- HISTORIOGRAPHY -- CONGRESSES